IMPROVING THE QUALITY OF LIFE OF THE POPULATION BASED ON THE DEVELOPMENT OF ENTREPRENEURIAL ACTIVITY - Ergasheva, Nasiba Rahmatullayevna; Barotov, Komiljon Farhod oʻgʻli (THE INNOVATION ECONOMY, 2026)
This article analyzes the role of entrepreneurship in the economic system and its impact on the quality of life of the population. The issues of increasing employment, expanding sources of income, and strengthening regional economic activity through the development of entrepreneurship are discussed. The innovative activities of small business entities, factors for increasing competitiveness, and the effectiveness of support mechanisms created by the state are also studied. According to the results of the study, it is justified that through the systematic development of entrepreneurship, it is possible to ensure a sustainable increase in the social well-being and quality of life of the population.